Finite element analysis of axially loaded pierced profiled composite panel - Lim, See Chaw (2010)
In this new era, the usage of profiled steel sheeting is getting popular in the construction. The usage of composite profiled steel sheeting can reduce the duration of construction and it is easy during installation. Besides, this two outer skins of profiled steel sheeting with an in filled of concrete also can act as load-bearing wall. Therefore, axial load, lateral load and in plane loads can be carried through to the composite system once the concrete has hardened. The pierced composite profiled steel sheeting such as doors and windows will affect the performance of the composite wall that will cause strength reduction. This project is to investigate the behavior of composite profiled steel sheeting panels under axial load by using finite element method. Six types of model have been analysed in this project and the dimension is 760 mm width and 1000 mm height with standard pierced size of 210 mm x 260 mm. All models are tested under linear analysis which will resulted the deformed mesh, maximum stress and strain and critical buckling load by using LUSAS Modeller 14.0 finite element software. The finite element analysis shows that Spandek composite panel is better than Trimdek composite panel.